Od glottodydaktyki polonistycznej do edukacji różnojęzyczności – badanie potencjału językowego. Raport z pilotażu .......... 125 - Prizel-Kania, Adriana; Terka, Beata (Z zamiłowania i pasji: Monografia zbiorowa poświęcona Profesorowi Władysławowi T. Miodunce, 2025)
FROM TEACHING POLISH AS A FOREIGN LANGUAGE TO PLURILINGUAL EDUCATION – RESEARCH IN LANGUAGE APTITUDE. A PILOT STUDYThe concept of plurilingual competence and its development has been present in the field of language learning and teaching (also in Polish studies) for several decades; however, the competence itself has not become a subject of systematic development. The text at first discusses issues related to plurilingualism and interculturality, with reference to works of Professor Władysław Miodunka, in which he anticipated the present changes in language education. In the second part the results of an experimental study are presented. Individuals proficient in several foreign languages and possessing advanced metalinguistic knowledge with no prior experience with learning Polish were asked to complete specially designed receptive language tasks in Polish. Then, they were asked to write a short text in this language. The linguistic analysis of their language production let us draw conclusion that it is possible to develop plurilingual competence within the framework of teaching Polish as a foreign language.